The Effect of Artificial Intelligence and Gamification on Online Purchase Intention Mediated by Customer Experience: Study on Indonesian Marketplace Users - Raeni Dwi Santy; Muhammad Iffan (Universitas Mercu Buana, 2023)
Objectives: This study aims to analyze the effect of Artificial intelligence and gamification on online purchase intention, as well as the role of customer experience as a variable that mediates the effect of artificial intelligence and gamification on online purchase intention. The marketing approach in today's era tends to lean towards digital personalization using Artificial intelligence and gamification to improve customer engagement and experience. This is ongoing with the fast rate at which technology has been expanding. The development of artificial intelligence has increased consumer happiness even more, making it even more crucial in the contemporary environment. Also, Gamification has clearly been identified as a method of influencing consumer behavior. The use of game design elements in non-game contexts is known as gamification. Gamification and persuasive technologies have been used for business purposes and to influence customer behavior.Methodology: The method used in this study is a quantitative method using survey research with marketplace users in Indonesia as the object of the research. Data collection which was used is the cross-sectional method by distributing online questionnaires from Google Forms. The research sample was selected using the purposive sampling method in order to obtain 272 respondents from various users (Tokopedia, Shopee, Lazada, Blibli, and Bukalapak users). The data analysis that is used is the path analysis Structural Equation Model (SEM) by SmartPLS 3.0 software. The first stage in data analysis is to recapitulate data on the characteristics of the respondents. The next step is to measure the validity and reliability using discriminant validity, convergent validity, composite reliability, and Cronbach's alpha. Then, to test the inner model, a Goodness of Fit test was carried out through R-Square and significance testing by interpreting path analysis values, T-values, and P-Values.Finding: In this research conducted on marketplace users in Indonesia, it was found that Artificial Intelligence and Gamification are determinants of Customer Experience but these two variables cannot directly support Online Purchase Intention. Further findings indicate that Customer Experience can be an important determining factor for Online Purchase Intention. Customer experience can strengthen the online purchase intention among marketplace users.Conclusion: The result of this study shows that Artificial intelligence and gamification cannot affect online purchase intention directly but artificial intelligence and gamification can affect online purchase intention indirectly through customer experience